Asymptomatic Mesenchymal Hamartoma of the Chest Wall in Child With Fluorodeoxyglucose Uptake on PET/CT—Report of a Case - Okamoto, Kentaro (Int Surg, 2015)
We had experience with a case of mesenchymal hamartoma of the chest wall (MHCW) with fluorodeoxyglucose (FDG) uptake on positron emission tomography/computed tomography (PET/CT). We reported the first case of asymptomatic MHCW in a child with preoperative PET/CT. Mesenchymal hamartoma of the chest wall is a rare benign tumor that usually presents as a visible chest wall mass or respiratory problems secondary to compression of the lung in early infancy. It is often reported that malignant transformation is extraordinarily rare. Positron emission tomography/CT is useful for diagnosis of malignancy. There is no report of MHCW in a child with preoperative PET/CT before. We examined an asymptomatic 1-year-old girl with an incidental finding on a chest x-ray. Scans of CT and PET/CT were performed before surgical resection. After surgery, the resected tumor was examined histologically. Chest x-ray and CT scan of the chest confirmed a 25- × 20-mm round shaped intrapleural mass containing calcification and destructing the rib, arising from the third rib. Scan of PET/CT demonstrated the mass with light FDG accumulation. Histologically, the mass was homogenous, with thick funicular of hyaline cartilage interdigitating with scattered fiber. There were no malignant cells. No malignant MHCW was demonstrated in the mass, with light FDG accumulation by PET/CT. PET/CT might be a useful tool to distinguish malignant MHCW in children.